Perancangan Sistem Informasi Penggajian Terintegrasi Berbasis Web (Studi Kasus di Rumah Sakit St. Elisabeth) - Cosmas Eko Suharyanto; Joni Eka Chandra; Fergyanto E Gunawan (Jurusan Sistem Informasi, Fakultas Teknologi Informasi, Universitas Andalas, 2017)
This study aims to analyze and provide a solutive proposal to the payroll system at St. Elisabeth Hospital which is not implemented an integrated system and still uses manual calculations. By Using Database Management System and designing web based interface then payroll system become more effective and efficient. Integrated system solves data redundancy problems and integrates payroll sub-sub systems. Integrated process allows for the integration of reports with fast processing and minimizing problems caused by human error. The effectiveness and efficiency of the payroll system will have an impact on optimal hospital services.